Cheng wei dong xue - Chuanbeimu 1983- (Catch, 2021)
"The first collection of drawings and stories in six years by leading Taiwanese illustrator Inca Pan. Designed by TENG Yu of Paper travel in a dazzling showcase of the art and craftsmanship of physical publishing. This collection of 51 intricate illustrations and 51 fantastical short stories builds worlds of fantasy that are rich in metaphor and symbolism. The illustrations and drawings can be appreciated separately, but gain another level of meaning when viewed together. The poetry of thes words is arresting, the beauty fascinating." (Publisher)